Tactical measures set to improve the import substitution process in the field of Russian pharmaceuticals - L. V. Orlova; P. V. Zobov (Вестник университета)
The article deals with the problems of a high share of import dependence in the pharmaceutical and medical industry of the Russian Federation, leading to a decrease in the security of the state and public health, to the actualization of providing modern and high-quality Russian medicines issues. The study analyzes the causes of the current situation in the pharmaceutical and medical industry in Russia. Based on the information received, the policy of state actions for the purchase of imported substances, raw materials, equipment from China and India is analyzed using modern data processing methods. Guided by modern tools for managing business strategies in industry, tactical measures that will speed up the process of import substitution through the formation and effective use of the research, technological and production potential of the state are proposed. A set of tactical measures to improve the import substitution process in the field of Russian pharmaceuticals is also presented. The assessment of the proposed tactical measures to improve the process of import substitution in the field of pharmaceuticals, which is designed to solve important social, economic and strategic tasks, has been carried out.